Investigation of biological activities of the flowers of Lagerstroemia speciosa, the Jarul flower of Bangladesh - Tasnuva Sharmin; Md. Shahidur Rahman; Habiba Mohammadi (BMC, 2018)
Abstract Background Lagerstroemia speciosa (L.) Pers. (Family: Lythraceae) is used in traditional medicine in the treatment of diarrhea, diabetes and other diseases. The study was performed to conduct antioxidant, cytotoxic, thrombolytic, membrane stabilizing, antimicrobial, peripheral and central analgesic and hypoglycemic activity assays and phenobarbitone sodium-induced sleeping time test using crude methanol extract of flowers of L. speciosa and its different partitionates. Method The antioxidant potential was evaluated by determining the ability of the samples to scavenge 1, 1-diphenyl-2-picrylhydrazyl (DPPH) free radical. The cytotoxic potential was examined following the procedures of brine shrimp lethality bioassay. Thrombolytic potential was assayed using streptokinase as standard. The samples were subjected to membrane stabilizing activity assay under heat induced condition. Antimicrobial potential was observed by disc diffusion method. The ability of the extract to inhibit writhing induced by acetic acid was determined in peripheral analgesic activity assay. The extract was also tested for central analgesic and hypoglycemic activities by tail flicking and tail tipping methods in Swiss albino mice model, respectively. CNS depressant activity was evaluated by an assay in which sleep was induced in mice using phenobarbitone sodium. Results The chloroform soluble fraction of L. speciosa extract demonstrated the highest antioxidant activity (IC50 = 4.20 ± 0.41 μg/ml) while the most prominent cytotoxic potency was showed by hexane soluble fraction (LC50 = 2.00 ± 0.31 μg/ml). Among the test samples, the carbon tetrachloride soluble fraction induced clot lysis (64.80 ± 0.27%) and prevented heat induced haemolysis (41.90 ± 0.10%) to the maximum extent. The largest zone of inhibition (19.0 mm) against Staphylococcus aureus, was also observed for the same fraction. In peripheral analgesic activity assay, 16.68% inhibition of writhing was documented for the L. speciosa extract (400 mg/kg body weight dose). The extract (400 mg/kg dose) also reduced blood sugar level by 56.12% after three hours of administration of glucose solution. In CNS depressant activity assay, mice of the sample group slept for shorter period of time compared to control group. Conclusions From our investigation, it can be suggested that, the extract should be further studied for possible phytochemicals responsible for the observed biological activities.